PENGARUH HIPOKSIA ISKEMIK PRENATAL TERHADAP UKURAN MIOKARDIUM TIKUS RATTUS NORVEGICUS GALUR SPRAGUE-DAWLEY - Muhammad Hadiyan Rasyadi (FKU 16 UMY 112, 2016)
Background: Hypoxia is a condition to the low concentration of oxygen in the cells or tissues that may threaten the survival of cells. Cells can adaptation, injury, or death. Prenatal hypoxia is still a major cause of morbidity and mortality in developed and developing countries based on datafrom World Health Organization (WHO). Oxygen is an important component in the metabolism of the myocardium. This study aimed to research the effect of prenatal hypoxic ischemic on thickness of myocardium. Methods: This research use experimental post -test control group design. This study used child Rattus norvegicus of Sprague-Dawley strain obtained from a pregnant female Rattus norvegicus who was induced until prenatal hypoxic ischemic happen in different age gestation by ligating the right uterina artery. Female Rattus norvegicus were divided into 3 groups, K is a control group that was not induced prenatal ischemic hypoxic, P1 group was given induced prenatal ischemic hypoxia on the parent who is pregnant at the age of 7 days, P2 group was given induced prenatal ischemic hypoxia on the parent who is pregnant at the age of 11 days. After that put the incision from the heartof the rat into the object glass and coloured it with Hematoxylin Eosin stain and then measured it under the microscope. Result: Prenatal hypoxic ischemic induction shows changes in the size of the myocardium by increasing the size. One - Way ANOVA test showed a significant increase (p=0,000). Post Hoc test showed differences in the increase of the size of the heart myocardium significantly between groups K-P1(p=0,000), K-P2(p=0,000), P1-P2(p=0,097). Conclusion: There is a significant difference in the size of the thickness from the myocardium rats Rattus norvegicus strain Sprague - Dawley induced prenatal hypoxic ischemic by ligating right uterine artery between the intervention group and control group. There is an increased thickness of the myocardium according to the time of exposure, the earlier the exposure is given, will increase more significant influence.